Fostering the retention of talented and skilled employees by understanding the motivators of employee turnover intention from a South African SMME perspective - Edayi, Juliet (University of the Witwatersrand, Johannesburg, 2024)
Current small, micro and medium-sized enterprises (SMMEs) are concerned about understanding the preliminary factors that prompt employees to leave their organisation (i.e., labour turnover intention) rather than to wait, only to be left to deal with the disruptive and costly consequences of actual employee turnover. The extant literature has widely provided evidence to justify that employee turnover is very destructive and presents many costs for organisations due to its counterproductive nature. South African small and micro businesses constantly endure high rates of employee turnover as other businesses (especially big companies) are frequently poaching highly skilled workers. This burden has made it increasingly challenging for SMMEs to keep, particularly highly skilled and high-performing employees, whose talents are highly sought after and are paramount to their firm’s overall success and sustainability. Therefore, this study was conducted from an SMME context so as to equip small and micro business employers with fresh insights on how proactively adjust their employee retention strategies and foster their continued survival and long-term growth. Moreover, the South African labour market has a limited number of high-performing and brilliant employees who eventually become assets to the business once hired, thus creating a need to retain such talented personnel. The shortage of skilled labour coupled with the high costs of attracting, hiring and training new employees proffers a compelling need for scholars to actively direct their research attention to unravelling this phenomenon of labour turnover intention. Research outputs will positively equip SMME practitioners with the relevant and proven information for them to devise well-informed retention strategies before employees’ intention to quit the organisation manifests itself into an actual turnover. This study sought to achieve a meaningful understanding of the interplay between the complex relationships that exist between the selected variables and to establish how this comprehension can aid SMME practitioners in effectively reducing employee turnover rate to a reasonable proportion. For this study to establish this ultimate goal, an empirical investigation was done amongst employees in selected SMMEs in Gauteng province of South Africa. A conceptual framework that depicted all the relationships was developed and several hypotheses were formulated based on the evidence from the extant literature. This study utilised a cross-sectional research design through a quantitative-based method. A structured questionnaire was formulated and was administered in-person, and additionally distributed via emails. Data was gathered through non-probability convenience sampling, whereby 338 valid responses were received from employees across the selected SMMEs in Gauteng. iv Descriptive statistics (e.g., item analysis, Cronbach’s alpha computation) and bivariate correlation analysis were analysed using SPSS v 28 and inferential statistics were analysed through Structural Equation Modeling was undertaken using AMOS v 28. While the findings of this study corroborated the outcomes that were submitted by earlier scholars, some fresh and exciting directions in the associations between specific variables were established. This study eventually submitted a unique conceptual model that depicts the validated interactions between the study variables. It is believed that the confirmed associations detailed in the conceptual model will be used as guidelines for small and micro business practitioners to meaningfully and effectively manage employee turnover intentions while simultaneously fostering the retention of talented and high-performing workers. This investigation concluded by recommending that a similar study must be replicated using a mixed-method approach that applies probability sampling and longitudinal research design so as to address the methodological shortcomings that characterised this study.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Faculty of Commerce, Law and Management, School of Business Sceinces, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Employee retention; Human talent; Labour turnover intention; SMMEs; South Africa; SDG-8: Decent work and economic growth